A sustainability assessment of the modern method of construction in Saudi Arabia - Almutairi, Kamel; Alahmadi, Ramzi; Halawani, Ahmed T. M.; Almutairi, Yasir; Alsehaimi, Abduallah (Frontiers in Sustainable Cities, 2024)
By 2030, the Kingdom of Saudi Arabia (KSA) is seeking to increase homeownership to 70%. This has led to a considerable investment in residential construction, with the Housing Ministry establishing a stimulus program to enhance the use of Modern Methods of Construction (MMC). These technologies offer several benefits, including cost and time reduction, improved quality and productivity, and job creation. This study quantitatively analyzes the economic impacts of MMC adaptation on the Saudi economy using the Global Trade Analysis Project (GTAP) model. It considers incentives to adopt MMC, its technological advancements, and the skills currently available in the Saudi labor market. Moreover, the embodied carbon emissions of MMC are calculated using the Input-Output Life Cycle Assessment Approach (IO-LCA); the detailed environmental emissions from the transportation phase, accounting for material reduction, are assessed using the COPERT model and compared to conventional construction. The results reveal an increase of 1.92% in Saudi GDP, along with improved welfare of $28.5 billion and a notable increase in the sectors related to construction. Job creation is demonstrated by an increase in the employment of unskilled and skilled labor by 2.02% and 1.5%, respectively. The paper concludes that MMC's total embodied carbon emissions were approximately 77 million metric tonnes CO2, while its transport-related emissions are less than conventional approaches.